The EU Internal Market and the Transformation of Energy Systems to Sustainability - Erik Gawel; Sebastian Strunz (Intereconomics, 2019)
Sustainability requires taking the lasting effects of current actions into account, while acknowledging uncertainty over future preferences and technology. In other words, it is a long-term issue
Keywords: 330